Me ajudeeeeem!!!
Dou melhor resposta.
Anexos:
![](https://pt-static.z-dn.net/files/d1f/152108ae7326df9daf00835ef4531cea.jpg)
EmperorEmanuel:
hi
Soluções para a tarefa
Respondido por
4
Resposta:
f(x)=x^2-2x+2
f(-1)=(-1)^2-2*(-1)+2= 1+2+2= 5
f(0)=0-2*0+2=2
f(1)=1^2-2*1+2=1-2+2=1
f(2)=2^2-2*2+2=4-4+2=2
f(3)=3^2-2*3+2=9-6+2=5
Explicação passo-a-passo:
Respondido por
0
fala ae camilaaaaaaaaa
Perguntas interessantes
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Biologia,
8 meses atrás
Artes,
9 meses atrás
Português,
9 meses atrás
Inglês,
1 ano atrás
Artes,
1 ano atrás